Pengaruh Harga, Promosi Dan Saluran Distribusi Semen Gresik Terhadap Minat Beli Konsumen (Studi Kasus di Distributor PT Abadi Putera Wirajaya) - Widya Purnamasari; Ahadiati Rohmatiah; Mintarti Indartini (Universitas Merdeka Madiun, 2021)
Abstract— The existence of PT Abadi Putera Wirajaya Karesidenan Madiun as a distributor must be used as the spearhead of the marketing of Semen Gresik products by increasing consumer buying interest. This study aims to determine the partially and simultaneously influence of price, promotion and distribution channels on consumer buying interest in Semen Gresik products at distributor of PT Abadi Putera Wirajaya Karesidenan Madiun and the variables that have a dominant influence on consumer buying interest in this products at distributor of PT Abadi Putera Wirajaya Karesidenan Madiun. The population in this study were all distributor channels in PT Abadi Putera Wirajaya Karesidenan Madiun in 2020, totaling 137 distributors. The sample in this study was 102 distributors whose size was determined by the Slovin formula. Sampling using random sampling technique. The research instrument used a questionnaire. The data analysis technique used validity and reliability test, classical assumption test, coefficient of determination analysis and hypothesis testing using t test, F test and standardized coefficients test. The results of the study are: 1) Price, promotion and distribution channels variables partially influences consumer buying interest in Semen Gresik products at distributor of PT Abadi Putera Wirajaya Karesidenan Madiun, 2) Price, promotion and distribution channels variables simultaneously influences consumer buying interest in Semen Gresik products at distributor of PT Abadi Putera Wirajaya Karesidenan Madiun, 3) Promotion is a variable that has a dominant influence on consumer buying interest in Semen Gresik products at distributor of PT Abadi Putera Wirajaya Karesidenan Madiun. Keywords—: Price; Promotion; Distribution Channels; Buying Interes.